Pengaruh Lama Perendaman Air Terhadap Perkecambahan Jagung - Inca Paskahlia Waruwu; Natalia Kristiani Lase (CV. SINAR HOWUHOWU, 2025)
Corn (Zea mays L.) is an important food crop whose successful cultivation largely depends on seed germination. Water plays a crucial role in germination by activating seed metabolism through the imbibition process. This study aimed to examine the effect of soaking duration on the speed and quality of corn seed germination. The research employed a completely randomized design with four soaking durations (0, 6, 12, and 24 hours), each replicated three times. Corn seeds were soaked according to the treatment times, then germinated on wet cotton media and observed for seven days. Parameters measured included germination percentage, radicle emergence time, and seedling length. Results showed that soaking duration significantly influenced all observed parameters. Soaking for 12 hours produced the best results with the highest germination percentage, faster radicle emergence, and optimal seedling length compared to other treatments. Short soaking times were insufficient to stimulate imbibition, while excessively long soaking reduced germination percentage due to oxygen deficiency and risk of seed decay. In conclusion, soaking corn seeds for 12 hours is recommended as the optimal duration to improve germination success. These findings can serve as a guideline for farmers to enhance seedling techniques for corn.